2015
DOI: 10.1038/ejhg.2015.89
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological, clinical and biochemical characterization of the p.(Ala359Asp) SMPD1 variant causing Niemann–Pick disease type B

Abstract: Niemann-Pick disease type B (NPDB) is a rare, inherited lysosomal storage disorder that occurs due to variants in the sphingomyelin phosphodiesterase 1 (SMPD1) gene and the resultant deficiency of acid sphingomyelinase (ASM) activity. While numerous variants causing NPDB have been described, only a small number have been studied in any detail. Herein, we describe the frequency of the p.(Ala359Asp) variant in the healthy Chilean population, and determine the haplotype background of homozygous patients to establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 28 publications
1
25
0
1
Order By: Relevance
“…These and other findings have assisted physicians, genetic counselors and families in predicting the phenotypic outcome in individual NPD patients, and in the future may lead to large-scale screening for this disorder in specific populations. For example, one particularly interesting recent study examined a single mutation (A359D) that occurs in >90% of type B patients in Chile [61]. Screening for this mutation among healthy individuals living in Santiago indicated that the carrier frequency for type B NPD within Chile was ~1/106, predicting a disease incidence of ~1/45,000.…”
Section: Molecular Geneticsmentioning
confidence: 99%
“…These and other findings have assisted physicians, genetic counselors and families in predicting the phenotypic outcome in individual NPD patients, and in the future may lead to large-scale screening for this disorder in specific populations. For example, one particularly interesting recent study examined a single mutation (A359D) that occurs in >90% of type B patients in Chile [61]. Screening for this mutation among healthy individuals living in Santiago indicated that the carrier frequency for type B NPD within Chile was ~1/106, predicting a disease incidence of ~1/45,000.…”
Section: Molecular Geneticsmentioning
confidence: 99%
“…Although NPA and NPB are pan-ethnic, NPA is more frequent in individuals with Ashkenazi Jewish ancestry than in the general population, with an estimated carrier frequency close to 1:80 and a disease incidence of 1/40,000 (Schuchman and Desnick, 2014 ). In other populations, such as in Chile, the carrier frequency for the type B mutation A359D occurs in 90% of patients close to a 1:106 rate, predicting a disease incidence of 1/45,000 (Acuña et al, 2016a , b ).…”
Section: Np Diseasesmentioning
confidence: 99%
“…More than 180 pathogenic mutations in the SMPD1 gene in patients with NPA and NPB have been identified, which are concentrated in exon two (Schuchman and Desnick, 2017 ). Recently, the ASMase crystal structure has been determined in humans (Xiong et al, 2016 ) and mouse (Gorelik et al, 2016 ), which may facilitate genotype-phenotype mutation analysis (Acuña et al, 2016b ; Zampieri et al, 2016 ).…”
Section: Np Diseasesmentioning
confidence: 99%
“…Particularly, both p.L304P and p.R498L are frequent Ashkenazi Jewish mutations and have been clearly associated to the severe NPA phenotype in this population [Levran et al., , 1992]. However, 12 mutations (p.R230C, p.W246C, p.D253H, p.D253E, p.A283T, p.Q294K, p.L343P, p.A359D, p.M384I, p.H423Y, p.H577R, and p.R602P) cause a severe impairment of ASM activity and were found in homozygosity or in association with another severe mutation in NPB patients [Simonaro et al, , Pittis et al., ; Pavlů‐Pereira et al., ; Desnick et al., , Hollak et al., , Acuna et al., ]. It is worth noting that eight of them (p.R230C, p.D253H, p.D253E, p.Q294K, p.L343P, p.M384I, p.H423Y, and p.H577R) were found in NPB patients with an intermediate clinical phenotype [Simonaro et al, , Pittis et al., ; Pavlů‐Pereira et al., ; Desnick et al., , Hollak et al., ].…”
Section: Genotype–phenotype Correlationmentioning
confidence: 99%